Analysis of extreme rainfall and floods in Colombo under climate change scenarios - Niroshinie, Malawara Arachchige Chamila; Babel, Mukand Singh; Sutat Weesakul; Perret, Sylvain Roger; Herath, Srikantha; Ministry of Foreign Affairs,Norway (Pathum Thani, Thailand : Asian Institute of Technology, 2010)
Colombo, the commercial capital of Sri Lanka is located in the flood plains of Kelani River,which makes Colombo area more vulnerabledue to flooding duringthe monsoon seasons.Furthermore, it has beenidentified that Colombo has undergone climate changes over the past years and very random change of rainfall anomalies had been observed. However, no research had beencarried out on analyzing extreme flood scenarios which can happen due to climate change conditionsin future. This study focused on analyzing the extreme flooding scenarios due to climate change in Colombo area. Specific objectives were, to analyze future climate conditions in Kelani basin with different GCM data, to define extreme rainfall scenarios for Kelani basin taking climate change into account, to model and simulate food inundations in Colombo area under extreme rainfall scenarios and to propose adaptation measures to reduce the impacts in Colombo area.Selection of the best GCM, which can represent the trend of rainfall in Colombo area, was done prior to analyzing climate change impacts to the study area. With compared to the observed data for the baseline and GCM data for the base line, CSIRO-Mk2 was the best among considered GCMs. Delta change method and Statistical DownscalingModel were used to downscale the GCM data. Aseasonal variation of future rainfall was observed with downscaled rainfall data.Frequency analysis was done for annual maximums of downscaled daily rainfall data to obtain the extreme events.Flood ModelingSystem (FMS) developed by UN University, JapanwithTokyo University, JapanandNippon Koei Geographic Analysis System (NKGIAS) was used for flood inundation modeling in Colombo area (lowerreach of Kelani River). According to the flood inundation modeling results, future flood events will createmore inundations than the past events. Therefore, possible adaptation measures especially non structural measures were suggested accordingly
A thesissubmitted in partial fulfillment of the requirementsfor thedegree of Master of Engineeringin Water Engineering and Management
Thesis (M.Eng.) - Asian Institute of Technology, 2009
Keywords: Rain and rainfall -- Environmental aspects -- Sri Lanka -- Colombo; Floods -- Environmental aspects -- Sri Lanka -- Colombo; Climatic changes -- Sri Lanka -- Colombo